Hydrochemical and isotopic interpretation of thermal waters from the Felgueira area (Central Portugal) - Morais, Manuel (2010)
The hydrothermal system of Felgueira has long been appreciated for the recreational and therapeutic benefits of the thermal baths. In order to protect and maintain these thermal resources it is necessary to understand the characteristics of these waters and determine its origin and that of its solutes. In this paper we use chemical and isotopic data as tools for addressing some of those questions. Early Holocene meteoric waters reacted, at low reservoir temperatures, with minerals from a granite aquifer, in an environment with available deep CO2, thus acquiring a sodium bicarbonate-chloride composition, with alkaline and strongly reducing characteristics. Biogenic sulphate reduction results in a wide variation of the S isotopic composition of both oxidized and reduced sulphur species. The drawdown imposed by exploitation wells results in some degree of vulnerability of the hydrothermal system.